Changes in soil organic carbon after burning in a forest-savanna edge (2017)
Soils are one of the largest terrestrial pools of carbon, yet there is still little understanding of spatial variability for ecosystems in the tropics. Fire plays an important role in Neotropical savannas ecosystems and significantly contribute to global greenhouse gas (GHG) fluxes. Nevertheless, the impacts of burning on soil carbon is still uncertain in Latin America. We compared soil organic carbon (SOC) in the first 20 cm depth in savannas in pre and post fire conditions along a forests-savanna edge typically present in these landscapes of the northern South America. We established 8 transects of 20 m longitude along the border with 1m2 plots sampled every 4 m. SOC pre-disturbance was on average 1.794 (±SE 0.043) and the minimum value found (1.08%) was registered 6 months after the burning. Our results show that both the influence of the distance to the edge and the time of burning affect negatively the SOC and also there is a significant interaction between both variables. Our results provide improved estimates of the effect of fire on soil carbon stocks and its highly dynamic nature. We believe these finding will be a step to help better estimate GHG in this type of heterogeneous landscapes. Further it provides a tool for understanding C dynamics under a climate change context with predicted increased fire frequency, extent and severity.